Toward a Typology of Diachronic Phonological Change in Bantu Languages - Nurse, Derek (Linguistica Atlantica, 1987)
There has been much recent work on explaining different types of phonetic and phonological processes. At the same time our overall knowledge of the world's languages is greatly expanding. Despite this, published statements about diachronic processes still tend to be largely based on long established Indo-European facts. This paper attempts to make a contribution to that imbalance by considering phonetic/phonological processes in a complete set of (non-Indo-European, Bantu) languages in a delimited geographical area (eastern Africa). It looks specifically at the diachronic processes needed to derive the contemporary languages from Proto-Bantu. Each process is identified, outlined, its relative frequency assessed, and, where possible, parallels are drawn to similar phenomena elsewhere. We do not attempt to indicate the interaction of the processes nor their implication for contemporary languages. It is hoped that this represents a small addition to the pool of knowledge on which future analyses are based.